The Influence of Brand Image and Product Quality on Purchasing Decision - Selvia, Selvia (ADPEBI, 2022)
The author's purpose in conducting this research is to determine and analyze the influence of brand image and product quality on purchasing decisions. The method used in this research is a quantitative research method. The data collection method used by the author in this study was through a questionnaire and by using the Slovin formula and obtained 96 samples. From the results of the study, it was found that partially the brand image variable had a tcount value of 4.837 > 1.985 and sig 0.000 < 0.05 and the Product Quality variable had a tcount value of 2.123 > 1.985 and sig 0.036 < 0.05, so it was concluded that brand image had a significant effect on decisions and quality. the product has a significant effect on purchasing decisions, while simultaneously the brand image and product quality variables have an Fcount of 16.943 > 3.09 so it can be concluded that the brand image and product quality variables have a positive and significant effect on purchasing decisions.